Switzerland : Selected Issues. (IMF Staff Country Reports; Country Report, 2001)
In Switzerland, institutionalized expenditure restraints via budget rules have been in use for some time at the cantonal level and for various city budgets. Under the proposed rule for the federal government, spending limits are set by the government although the parliament is primarily allowed to make only compositional changes in expenditure. Level changes require a qualified majority in parliament. With these requirements, the Swiss government aims to shift the political debate away from spending ceilings toward a debate about long-term spending trends.